Impacts of the Combined Pretreatment Using NaOH and Ozone on Enzymatic Hydrolysis and Morphology of Rice Straw - Li, H.Y.; Jin, M.; Huang, K.L.; Li, Z.G.; Liu, S.Q.; Liu, Y.N.; Wu, X.W. (Asian Journal of Chemistry, 2012)
The combined pretreatment of rice straw using NaOH and ozone followed by enzymatic hydrolysis was investigated in comparison with NaOH pretreatment. In order to measure the composition variance, the surface morphology of rice straw was investigated by the scanning electron microscopy. The combined pretreatment of rice straw increased the specific surface area and total pore volume, which could degrade the lignin polymer, solubilize hemicellulose and neutral detergent solubles. During the combined pretreatment of rice straw using NaOH and ozone, no measurable quantity of furfural and hydroxymethyl furfural has been detected. These chemical and morphological changes of rice straw lead to the increased access of cellulase to rice straw surface and the enhanced susceptibility to enzymatic hydrolysis. The conversed percentage of cellulose and hemicelluloses presented in combined pretreated rice straw is 92.6 %, while those of NaOH pretreated and untreated rice straw are 73.8 % and 52.5 %, respectively.